2013
DOI: 10.1590/s0066-782x2013005000001
|View full text |Cite
|
Sign up to set email alerts
|

Ecocardiografia de pacientes talassêmicos sem insuficiência cardíaca em tratamento com transfusões sanguíneas e quelação

Abstract: Background: Patients with thalassemia major present chronic hemolysis and require regular blood transfusions which may cause iron overload cardiomyopathy and chronic heart failure. Hemochromatosis is characterized by excessive iron accumulation in tissues, and heart involvement is the main cause of death in patients with thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…A recent study demonstrated a significant correlation between iron overload in the liver and pulmonary artery systolic pressure independent of LV filling pressures . conventional Doppler echocardiography and tissue Doppler allow for identifying left ventricular diastolic alterations in asymptomatic patients with thalassemia major (Rodrigues et al, 2013). In comparison, another investigation consisting 110 patients with thalassemia intermedia, overall mean ferritin levels were 1657±1477ng/ml which was lower than what we found in the present study (2419.13±1772.65ng/ml) that could be the result of less frequent and incorrect use of iron chelation in our patients (Aessopos et al, 2001).…”
Section: Discussioncontrasting
confidence: 83%
“…A recent study demonstrated a significant correlation between iron overload in the liver and pulmonary artery systolic pressure independent of LV filling pressures . conventional Doppler echocardiography and tissue Doppler allow for identifying left ventricular diastolic alterations in asymptomatic patients with thalassemia major (Rodrigues et al, 2013). In comparison, another investigation consisting 110 patients with thalassemia intermedia, overall mean ferritin levels were 1657±1477ng/ml which was lower than what we found in the present study (2419.13±1772.65ng/ml) that could be the result of less frequent and incorrect use of iron chelation in our patients (Aessopos et al, 2001).…”
Section: Discussioncontrasting
confidence: 83%
“…In response to the letter, we appreciate the interest shown and comments made on our work 1. We hope that our data will stimulate new research especially in the field of biventricular diastolic function in individuals with thalassemia major.…”
mentioning
confidence: 84%
“…An E/E' ratio ≥4 had high sensitivity and specificity for predicting RA pressure ≥10 mm Hg in non-cardiac surgery intensive care unit patients 4 . The current study 1 did not evaluate RV diastolic function and RA volume. Further studies should be conducted to assess RA volume and RV tissue Doppler diastolic parameters such as tricuspid E/E' ratio.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A standard echocardiography system (General Electric Medical Systems, Vivid 3) was used to measure cardiac structures as previously described and following American Society of Echocardiography recommendations [17], [18], [19], [20]. All echocardiograms were performed by the same examiner (JMBBF).…”
Section: Methodsmentioning
confidence: 99%